The Effect of Neck Exercises on Headaches of Adolescent : A Case Study of College Students in Kudus, Indonesia - Sukarmin; Mardiana, Sri Siska (The Indonesian Institute of Science and Technology Research, 2023)
Headache is a symptom that widely happen by all age groups including adolescents. According to the Global Burden of Disease (GBD) study, headache belongs the most common disorder occurring to adolescent. a Systematic Review (SR) study of 357 publications, globally the estimated prevalence of active headaches is about 52.0%. This study is to determine the effect of neck exercises on college students’ headaches. This methodology a quasi-experimental study which involve two group including 16 intervention groups and 16 control groups. The intervention group was given neck exercises for 4 weeks, while the control group was given headache education materials. Results of research there was a significant difference in headache before and after neck exercise in the intervention group (p value 0.015) and no significant difference in headache in the control group (p value 0.180). Neck exercises are quite significant in reducing college students' headaches.